호기성 분진중의 중금속 오염도에 관한 조사연구 - 임영욱 (연세대학교 보건대학원, 1988)
[한글] 대기오염에 의한 부유분진의 위해성은 오래전부터 논란의 대상이 되어 왔으며 이 성분중 중금속류에 대한 위해성은 빈번한 대상이 되어왔다. 아직 우리나라에서는 대기오염의 한 중요한 지표인 부유분진중의 인체에 유해한 것으로 알려진 호기성분진 (respirable dust)에 대한 규제를 실시하지 못하고 있는 실정으로 측정상의 어려운 점등을 이유로 총부유분진 (total suspended particulates)을 대상으로 삼고 있다. 호기성 분진은 주로 15μm이하의 미세한 크기의 분진으로 호흡기의 각 기관에 침착 된다. 따라서 도시 부유분진중 호기성분진과 그중의 성분, 특히 유해성물질을 파악하여 도시인의 건강상 위해성에 대한 평가(risk assessment)가 이루어져야 할 것이다. 본 연구에서는 도심의 대표적인 형태인 상업 및 교통혼잡지역인 신촌동의 한지점과 주거지역인 불광동의 한지점을 대상으로 대기부유분진의 입도별 분포와 그중의 중금속 12종에 대한 오염도를 조사분석 하였다. 부유분진은 high volume cascade impactor air sampler로 입도별 포집 및 측정을 하였으며 그중 중금속은 atomic absorption spectrophotometer와 inductively coupled plasma emission spectrophotometer로 측정하였다. 조사기간은 1987년 5월부터 1988년 3월까지 격월로 홀수달에 각기 포집하였으며 포집주기는 1주일씩으로 하였다. 1. 대기중 총부유분진 조사에서 신촌지역은 연평균 179.77㎍/㎡로 환경기준 150㎍/㎡보다 높은 오염도를 나타내었으며 2μm를 경계로 한 미세입자(fine particle)는 58.76%,조대입자( coarse particle )는 41.24%이었다. 불광지역은 연평균 130.43㎍/㎡의 오염도를 나타내었고 미세입자는60.30%, 조대입자는 39.70%를 나타내었다. 또한 난방기의 오염도가 비난방기에 비하여 높았다. 2. 대기 부유분진의 입도별 분포는 10.2μm이상의 입자가 15.12%, 4.2∼10.1μm는 17.72%, 2.1∼4.1μm는 8.40%, 1.3∼2.0μm는 11.25%, 0.69∼1.2μm 는 12.14%, 0.39∼0.68μm는 10.70% 그리고 0.38μm이하 입자가 24.67% 이었고, 입도별 분포양상은 4.2∼10.1μm에서 큰 봉(peak)을 1.2∼2.0μm에서 작은 봉을 그리고 0.38μm이하에서 다시 큰 봉을 나타내는 삼산형 (三山型) 이었다. 불광지역은 10.2μm이상의 입자가 13.68%, 4.2-10.1μm는 16.91%, 2.1∼4.1μm는 9.11%, 1.3∼2.0μm는 10.45%, 0.69∼1.2μm는 11.48%, 0.39∼0.68μm는 11.95% 그리고 0.38μm이하에서는 26.42%이었고, 입도별 분포양상은 4.2∼10.1μm와 0.38μm이하에서 봉을 이루는 이산형(二山型)이었다. 3. 10.1μm 이하 입자크기의 호기성분진(respirable dust)오염도 조사에서 신촌지역의 연평균 호기성분진의 농도는 152.59㎍/㎡로 총 부유분진의 약 85%정도이었다. 호기성분진에 대한 비호기성분진의 비는 5.61로 나타났다. 불광지역은 연평균 호기성분진이 112.56 ㎍/㎡로 총부유분진의 86%로 나타났다. 기성분진에 대한 비호기성 분진의 비는 6.31이었다. 4. 호기성분진의 중금속 오염도는 신촌지역에서 Fe이 0.628㎍/㎡, Zn은 0.317㎍/㎡, Pb는 0.214㎍/㎡, V은 0.175㎍/㎡, Se은 0.131㎍/㎡, Cu는 0.110㎍/㎡, Mn은 0.062㎍/㎡, Ni은 0.043㎍/㎡, As는 0.016㎍/㎡, Cd은 0.0066㎍/㎡, Cr은 0.0042㎍/㎡ 그리고 Hg은 0.00026㎍/㎡이었다. 각 중금속의 호기성분진에 대한 비호기성분진의 농도비는 Pb는 19.45, As는 16.00, Cd은 13.20, Cu는 7.86, Ni은 7.17, Zn는 6.89, Hg은 6.50, Se은 5.95, Mn은 5.64. Fe은 3.97, Cr은 3.82 그리고 V은 2.92로 나타났다. 불광지역에서 호기성분진의 중금속 오염도는 Fe이 0.735㎍/㎡, , Zn은 0.321㎍/㎡, Se은 0.168㎍/㎡, Pb은 0.167㎍/㎡, V은 0.144㎍/㎡, Cu는 0.119㎍/㎡, Mn은 0.053㎍/㎡, Ni은 0.032㎍/㎡, Cd은 0.0089㎍/㎡, Cr은0.0047㎍/㎡, As는 0.0025㎍/㎡ 그리고 Hg은 0.00044㎍/㎡이었다. 호기성분진에 대한 비호기성분진의 농도비는 Pb이 23.86, Cd이 14.83, Zn가 10.70, Hg이 8.80, Cu가 8.50, As는 8.33, Se은 6.72, Mn은 6.63, V는 5.76, Ni와 Fe은 5.33, 그리고 Cr은 4.27이었다. 5. 조사기간의 대기중 중금속 오염도는 대부분의 조사중금속에 대하여 신촌지역은 1987년 5월이 가장 높았고 불광지역은 1987년 7월이 가장 높았다. 6. 대기중의 입도별 중금속 오염도는 Cr, Fe, Mn 및 V의 농도가 조대입자에서 높았고 Cd과 Pb은 미세입자의 오염도가 높았다. 분진중의 중금속 함유량은 Cr, Fe 및 V이 조대입자에서 높았고 Cd, Hg, Pb, Se 및 Zn는 미세입자에서 높았다. 7. 오염 배출원의 추정을 위하여 중금속간의 상관관계를 분석한바 신촌지역은 Fe, Se 및 Mn간에 높은 상관관계를 나타내어 석탄과 가솔린 및 디젤에 의한 오염으로 추정되었고 불광지역은 Fe, Se, Hg 및 Mn간에 높은 상관관계를 나타내어 석탄과 석유연료인 벙커- C 및 중유에 의한 오염으로 추정되었다. 8. 조사지역의 중금속 오염도 변화조사에서 신촌지역은 Fe, Ni, Pb 및 Zn의 오염도가 다소 감소하는 변화를 보였으며 불광지역은 Cu, Mn 및 Zn은 감소한 반면 As, Fe 및 Se의 오염도는 증가하였다. 이상의 분석결과로 보아 서울시의 대기부유분진의 오염도는 높으며 그 중 특정한 중금속의 오염도가 높아 이에 대한 건강상 위해성이 평가되어야하며 그 대책이 요구된다. [영문] The harmful effects of suspended particulates in human health have long been the environmental study object of interest, especially those contained with heavy metals. Based upon the particle size, the suspended particulates can be classified to the non-respirable dust which has larger particle size and the respirable dust which has smaller particle size. Since the respirable dust are more harmful, it is desirable to have different regulation standards according to its size group. However, our country regulate only the total suspended particulate level presumably because of the difficulty of the measurement. The respirable suspended particulates has inhalable particle size, less than 15μm in diameter, which can be adsorbed to various parts of human respiratory organ. Naturally, it is important, for human health risk assessment, to figure out the portion of the respirable particulates among total suspended particulates and the kinds of harmful substances adsorbed to the former. In this study, two survey stations were chosen; one was in the Shinchon area which is the commercial district with heavy traffic and the other one was in the Bulgwang area. The total suspended particulates were differentially sampled by the different particle size group, the quantity of each particle size group was weighed and the concentration of 12 heavy metals adsorbed to the different particle size group was measured. The high volume cascade impactor was used for the sampling and the quantity measurement. The concentration of heavy metals was measured by atomic absorption spectrophotometer and inductively coupled plasma emission spectrophotometer. The investigation period was from May, 1987 to March,1985. Each sample was taken for 7 days by two month intervals. The results are sumnarized as follows : 1. The annual average concentration of total suspended particulates was 179.77㎍/㎡ in the air of the Shinchon survey station, which was higher than the national envirommental standards (150㎍/㎡). The total suspended particulates was divided to 2 size groups using the diameter size of 2μm as the splitting point; the percentage of the fine particle which diameter is smaller than 2μm was 58.76% and that of the coarse particle which diameter is larger than 2μm was 41.24%. The annual average concentration of total suspended particulates in the air of the Bulgwang survey station was 130.43㎍/㎡ ; the percentage of the fine particle was 60.30% and that of the coarse particle was 39.70%. 2. The particle size was divided further to 7 size groups, the percentage of each size group from the Shinchon air samples was as follows: >10.2μm, 15.12%; 4.2-10μm, 17.72%; 2.1-4.1μm, 8.40%: 1.3-2.Oμm, 11.25%: 0.69-1.2μm, 12.14%: 0.39-0.68μm, 10.70%; <0.38μm, 24.67%. The shape of the size distribution was trimodal which showed high peaks at 3 size groups: 4.2-10.1μm, 1.2-20μm, <0.38 μm. The Bulgwang air samples was as fellows: 10.2μm, 13.68%; 4.2-10.1μm, 16.91%: 2.1-4.1μm, 9.11%; 1.3-2.0μm, 10.45%; 0.69-1.2μm 11.48%; 0.39-0.68μm, 11.95%; <0.38μm, 26.42%. The shape of the size distribution was bimodal which showed high peaks at 2 size groups; 4.2-10.1μm, < 0.38μm. 3. The annual average concentration of the respirable suspended dust which diameter is less than 10.1 μm was 152.59㎍/㎡ from the Shinchon air samples; this was approximately 85% of the total suspended particulates. The ratio of the non-respirable suspended dust to the respirable one was 5.61. The annual average concentration of the respirable suspended dust from the Bulgwang ail samples was 112.56㎍/㎡; this was approximately 86% of the total suspended particulates. The ratio of the non-respirable suspended dust to the respirable one was 6.31. 4. The concentration of heavy metals adsorbed to respirable suspended dust from the Shinchon air samples was as follows; Fe, 0.628㎍/㎡; Zn, 0.317㎍/㎡; Pb, 0.214㎍/㎡; V, 0.175㎍/㎡; Se, 0.131㎍/㎡; Cu, 0.110㎍/㎡; Mn, 0.062㎍/㎡; Ni, 0.043 μ; As, 0.016 ㎍/㎡; Cd, 0.0016 ㎍/㎡; Cr, 0.0042 ㎍/㎡; Hg, 0.00026 ㎍/㎡. The ratio of heavy medals adsorbed to the non-respirable dust to those adsorbed to respirable one from the Shinchon air samples was as fellows : Pb, 19.45; As, 16.00: Cd, 13.20: Cu, 7.86; Ni, 7.17; Zn, 6.89; Hg, 6.50; Se, 5.95;Mn, 5.64; Fe, 3.97; Cr, 3.82; V, 2.92. The concentration of heavy metals adsorbed to respirable suspended dust from the Bulgwang air samples was as follows : Fe, 0.735 ㎍/㎡; Zn, 0.321㎍/㎡; Se, 0.168 ㎍/㎡; Pb, 0.167 ㎍/㎡; V, 0.144㎍/㎡; Cu, 0.119㎍/㎡; Mn, 0.053㎍/㎡; Ni, 0.032 ㎍/㎡; Cd, 0.0089㎍/㎡; Cr, 0.0047 ㎍/㎡; As, 0.0025 ㎍/㎡; Hg, 0.00044 ㎍/㎡. The ratio of heavy petals adsorbed to suspended dust to those adsorbed to respirable one from the Bulgwang air samples was as follows: Pb, 23.86: Cd, 14.83: Zn 10.70; Hg, 8.80; Cu, 8.50; As, 8.33; Se, 6.72; Mn, 6.63; V, 5.76; Ni and Fe, 5.33; Cr. 4.27. 5. During the study period, the concentration of all heavy metals investigated was the highest on May 1987 at the Shinchon survey station and on July, 1987 at the Bulgwang survey station. 6. The concentration of heavy metals was investigated in relation to the particle size. The higher percentage of Cr, Fe, Mn and V tended to be adsorbed to coarse particles, while Cd and Pb tended to be adsorbed to fine particles. In the content of heavy metals in total suspended particulates, the concentrations of Cr, Fe and V were high in coarse particles, while those of Cd, Hg, Pb, Se, Zn were high in fine particles. 7. Correlation coefficients analysis was performed to evaluate the pollution sources. In the Shinchon area, there were high correlations between Fe, Se and Mn, and consider to be originated from coals gasoline and diesel. In Bulgwang area, Fe, Ge, Hg and Mn showed high correlations between them and thus considered to be originated from coal, bunker-C and heavy oil. 8. During the study period the concentrations of Fe, Ni, Pb and Zn decreased in the Shinchon area. In the Bulgwang area, the concentrations ef Cu, Mn and Zn decreased while those of As, Fe and Se increased. According to the results mentioned above, the respirable dust in total suspended particulates had a significant level in the ambient air, especially with the high concentration of some specific heavy metals in content. Therefore risk assessment and control should be conducted on the basis of this study.
환경관리학과/석사